2018
DOI: 10.12659/msm.910860
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Subcutaneous Allergen Immunotherapy in Southeast Turkey: A Real-Life Study

Abstract: BackgroundSubcutaneous immunotherapy (SCIT) in allergic rhinitis (AR) and asthma is a very effective treatment, but adherence is still a serious problem. Studies addressing real-life adherence to SCIT are rare in the literature. The aim of this study was to evaluate the adherence to SCIT in AR and asthma.Material/MethodsThe medical records of patients prescribed SCIT for treatment of AR and/or asthma were evaluated. Patients who continued the SCIT treatment as prescribed were defined as adherent, patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In literature, results regarding demographic and clinical data are also very variable. Tat also has not found differences in age or gender between the two groups [23]. Rhodes found a significant correlation between age and gender: non-adherent patients were younger than adherent and males were more frequently non-adherents than females [12].…”
Section: (Please Insert Table 3 Here)mentioning
confidence: 94%
See 2 more Smart Citations
“…In literature, results regarding demographic and clinical data are also very variable. Tat also has not found differences in age or gender between the two groups [23]. Rhodes found a significant correlation between age and gender: non-adherent patients were younger than adherent and males were more frequently non-adherents than females [12].…”
Section: (Please Insert Table 3 Here)mentioning
confidence: 94%
“…Vaswani et al reported a rate of 40% of suspension due to SCIT costs, especially inadequate or nonexistent insurance coverage [25]. In his study, Tat also concluded that a main reason for SCIT suspension was the delayed reimbursement by health insurance [23]. [20].…”
Section: (Please Insert Table 3 Here)mentioning
confidence: 98%
See 1 more Smart Citation
“…Adherence to AIT is usually reported as the percentage of patients who maintain the treatment over a defined period of time. Some adherence studies report data for short periods of observation (6-12 months) [13][14][15], but guidelines recommend that in order to be effective, AITmust be continued for at least three years [5,6]; therefore, we deemed important to investigate the three-year treatment persistence. In our survey, 63.4% of patients completed the requested third year of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We considered only patients who started the treatment at least 3 years before to allow a sufficient observation period. Since reimbursement issues are deemed important for patients' adherence [10,13,14], we also compared the adherence of 59 patients coming from 3 centers with full reimbursement with that of 86 patients from 3 centers with no reimbursement at all. While "adherence" to SCIT is not a standard defined concept, we evaluated the number of patients treated for at least two years, the number treated for at least three years, the number treated for more than three years, and the number of drop outs after one treatment year only.…”
Section: Methods and Patientsmentioning
confidence: 99%